Village Apparatus Service Towards Community in Lambiheu Siem Village, Darussalam District, Aceh Besar Regency - Armiwa; Saputra, Furqan; Muklis (Dinasti International Journal of Digital Business Management, 2023)
Administratively, public services are one of the functions of the government in providing convenience for the community to exercise their rights and obligations. Public services are one of the responsibilities of government agencies, both at the central, regional and village levels. According to Law No. 6 of 2014 in article 11, it is stated that the Village Government consists of the Village Government and the Village Consultative Body. Meanwhile, according to Aceh Qanun no. 5 of 2003, the Village Government in the Province of Nanggroe Aceh Darussalam is a community unit that is under the mukim and has the right to organize and build its own household affairs. The formulation of the problem in this study is How is the service in Lambiheu Siem Village, Darussalam District, Aceh Besar Regency. How is the implementation of services in Lambiheu Siem Village, Darussalam District, Aceh Besar Regency. Theoretical Usefulness The results of this study can give birth to concepts and theories of administrative science, especially educational administration regarding organizational discipline and improving human resources. Practical Use The results of this study can contribute to decision makers in the implementation of discipline coaching in the community, especially for village officials, especially in Lambiheu Siem Village, Darussalam District, Aceh Besar Regency. This study uses a qualitative research method. The results of the study, The low level of effective and efficient service in Lambiheu Siem Village provides quality services to the community Slow and inefficient services, including the low work ability of Lambiheu Siem Village Apparatus due to the low level of education and training possessed by the apparatus is one of the inhibiting factors in the implementation of services in the village government. And the limited facilities and infrastructure to support the management of village services, such as the limited number of computers, inadequate work space in the hamlet government office.